Adaptation behavior of Bornean Orangutan (Pongo pygmaeus morio) reintroduction in Kehje Sewen Forest, East Kalimantan, Indonesia - SYAHIK NUR BANI; DYAH PERWITASARI-FARAJALLAH; SRI SUCI UTAMI ATMOKO; JAMARTIN SIHITE (Society for Indonesian Biodiversity, 2018)
Bani SN, Perwitasari-Farajallah D, Atmoko SSU, Sihite J. 2018. Adaptation behavior of Bornean Orangutan (Pongo pygmaeus morio) reintroduction in Kehje Sewen Forest, East Kalimantan, Indonesia. Biodiversitas 19: 989-996. Bornean Orangutan (Pongo pygmaeus) are grouped into three subspecies, including Pongo pygmaeus morio that spreads from Sabah to the southern parts of Mahakam River in East Kalimantan. Forest conversion is the main threat to the populations and habitat of Bornean orangutans. The orangutans which have been confiscated are going through rehabilitation process and reintroduction. Efforts should be taken to seize or confiscate orangutans as much as possible and return them to their natural forest habitat. This research aimed:  (i) to measure the development of rehabilitated orangutans in their post-release adaptation in native forest, especially in activity budget, diet, nesting and strata usage, in comparison to wild orangutans in the Danum Valley, (ii) to identify factors determining successful reintroduction of orangutans based on their final stage in rehabilitation process. Daily activities of four adult females of the orangutan with different types of last stage rehabilitation processes (pre-release island vs. cages) were compared during the monitoring of their behavior one year after their release in Kehje Sewen forest using focal animal sampling method. The analysis showed that diet pattern of all individuals resembled that of their wild orangutan counterparts. Meanwhile, activity pattern, strata usage, and nesting behavior was related to individual's capabilities and not determined by the type of final stage in the rehabilitation process. We assumed other factors should be considered as success factors of reintroduction.